Pengaruh Model Tutor Sebaya Berbantuan Media Pizza Pecahan Terhadap Hasil Belajar Materi Pecahan Kelas IV di SDN 2 Sukadana: The Influence Of Pair To Pair Method By Using Pizza Slice As A Medium Towards Students' Achievement Of Grade 4 In SDN 2 Sukadana - Detrianty, Fitria Rika; Hendrawan, Budi; Pratiwi, Anggia Suci (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research aimed to investigate the effect of pair to pair method towards the students’ achievement by using pizza slice as a media. The method of this research used Pretes-Posttest Group Design. This research used random sampling method. There were 22 students grade IV of SDN 2 Sukadana, 11 students as a control group and 11 students as an experiment group. The data collection of this research used pretest dan posttest, interview, and documentation. After the data gathered, those were analyzed used normalizaton test by kolmogrov-smirnov test and homogeneity test by fisher test. The result shows the pair to pair method gives significant effect toward students’ achievement by using pizza slice as a media. This can be seen in control group the students’ achievent in pretest 46.55 and posttest 64.36 and in the experiment group the students’ achievent in pretest 52.73 and posttest 72.36. Then Paired Sample method shows the hypothesis result sig 0,000 < 0,05, so HO is rejected and HA is accepted, which mean there is a significant effect from pair to pair method towards the students' achievements by using pizza slice as a media of grade IV of SDN 2 Sukadana.